2011
DOI: 10.1007/s10725-011-9647-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and impact of up- and down-regulating subabul cinnamyl alcohol dehydrogenase (CAD) gene on plant growth and lignin profiles in transgenic tobacco

Abstract: Both cDNA including 5 0 UTR and 3 0 UTR and genomic clones of cinnamyl alcohol dehydrogenase (CAD) were isolated and characterized from a pulp-yielding leguminous tree Leucaena leucocephala (LlCAD1). The deduced amino acid sequence shared high identity with orthologous sequences of Acacia mangium 9 Acacia auriculiformis (83%), Medicago sativa (83%), Nicotiana tabaccum (83%) and Aralia cordata (81%). Full length cDNA contained 78 bases of 5 0 UTR and 283 bases of 3 0 UTR, while the genomic clone contained 5 exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Down-regulating CCR affects the composition of soluble phenolics by increasing various ferulate derivatives in Arabidopsis , poplar, and tobacco [ 20 23 ]. A similar pattern was observed in CAD-downregulated tobacco [ 24 ]. Reducing lignin content may trigger signaling pathways that activate stress genes [ 25 ].…”
Section: Introductionsupporting
confidence: 81%
“…Down-regulating CCR affects the composition of soluble phenolics by increasing various ferulate derivatives in Arabidopsis , poplar, and tobacco [ 20 23 ]. A similar pattern was observed in CAD-downregulated tobacco [ 24 ]. Reducing lignin content may trigger signaling pathways that activate stress genes [ 25 ].…”
Section: Introductionsupporting
confidence: 81%
“…Numerous studies have reported that CAD is a key enzyme in the biosynthesis of lignin and plays an essential role in plant development associated with plant biomass ( Mitchell et al, 1994 ; Feuillet et al, 1995 ; Halpin et al, 1998 ; Bagniewska-Zadworna et al, 2014 ; Pan et al, 2014 ; Choi et al, 2016 ). Downregulation of CAD expression or its knockout causes a reduction of lignin, which leads to severe plant dwarfism and a decreased biomass ( Sirisha et al, 2012 ; Anderson et al, 2015 ; Ozparpucu et al, 2017 ; Ponniah et al, 2017 ) as well as decreased plant resistance to pathogens ( Bagniewska-Zadworna et al, 2014 ; Preisner et al, 2014 ; Rong et al, 2016 ). However, whether an increase in total lignin via CAD overexpression can affect the biosynthesis of terpenoids, such as artemisinin biosynthesis in A. annua , remains uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous characterization of CAD-deficient plants revealed a reddishorange coloration in the lignifying cells (Ralph et al, 1997;Sibout et al, 2005;Sirisha et al, 2012). For wild-type and fah1 plants, disruption of both CADC and CADD were required to observe this phenotype; however, lignified cells in cadc C4H-F5H are pigmented, and this coloration is even more intense in cadd C4H-F5H.…”
Section: Cad-manipulated Plants Have Typical Noncollapsed Vasculaturmentioning
confidence: 96%